If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + -3 = 9 + 4X Reorder the terms: -3 + 2X = 9 + 4X Solving -3 + 2X = 9 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. -3 + 2X + -4X = 9 + 4X + -4X Combine like terms: 2X + -4X = -2X -3 + -2X = 9 + 4X + -4X Combine like terms: 4X + -4X = 0 -3 + -2X = 9 + 0 -3 + -2X = 9 Add '3' to each side of the equation. -3 + 3 + -2X = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -2X = 9 + 3 -2X = 9 + 3 Combine like terms: 9 + 3 = 12 -2X = 12 Divide each side by '-2'. X = -6 Simplifying X = -6
| Z-17.2=17.3 | | s-17=1(s-5) | | 2X+3X-7+2=35-5X | | 12Y+48=7Y-47 | | 8x+14=x-16 | | 6y+7-2y+5=40 | | 8x-5+3x=28 | | 5(x+2)=6(x-1) | | 7x+21=4x-12 | | 8-3y=-11 | | 2(1-5x)+3(-1-x)-4(-7+2x)=-x | | 3x-4=65 | | 4x-2=x+15 | | 5x^2-35x+75=13 | | -6x+3=300 | | (1+3x)-(1-2)+(-11-7x)=5 | | 7n-21=28 | | 2h+14=20 | | x-(-4)=18 | | 2x+1/3=12/3-2x | | (2x+6y)+(4x-y)= | | 2x+6y+4x-y= | | 4x+3x=54 | | Y=4x+cwhatisy | | 6a+ab=0 | | (3)+0.7(3)=2.4+0.9(3) | | x+0.7x=2.4+0.9x | | 7+(2+n)=18 | | 12x^2-4= | | -16t^2+79t+5=0 | | 12x^2-4x-4=0 | | 42(1)-7(2(1)-1)=9(1)+8((1)+2) |